FINANCIAL SECURITY OF STRATEGIC BRANCHES OF THE NATIONAL ECONOMY: SUBSTANTIVE DECOMPOSITION AND SOURCES OF ANALYSIS METHODOLOGY - KUNYTSKA-ILIASH, MARTA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study focuses on the theoretical and methodological analysis of the basic provisions of state policy to ensure financial security of priority sectors of the national economy.The purpose of the article is to generalize the theoretical and methodological principles of analyzing the economic security of the state and economic security of the industry in order to form conceptual provisions of financial security of strategic sectors of the national economy, its decomposition and the principles of analysis methodology.The article emphasizes the urgency of considering the issues of economic and in particular financial security at the level of sectoral economic system. Particular emphasis is placed on the relevance of state policy to ensure financial security directly strategic (priority) sectors of the national economy. Based on the analysis of theoretical and methodological approaches to the formation of semantic and structural characteristics of economic security of the industry identified elements of methodological support for analyzing the financial security of strategic sectors of the national economy.The tasks of the methodology of financial security analysis of strategic sectors of the economy, such as financial and investment resources, proper financial condition, efficient use of capital, protection from financial risks and threats, development of financial subsystem, realization of potential in ensuring financial and economic development of the national economy. It is concluded that the elements of the logical-structural model of the methodology of analysis of strategic sectors of the national economy are the purpose, objectives, components, indicators, approaches and methods for analysis and evaluation.The applied significance of the research results is that such a concept as financial security of strategic industries has been introduced into the public policy system, which will allow to initiate measures to ensure it.The scientific novelty of the research results is that the elements of the logical-structural model of the methodology of analysis of strategic sectors of the national economy are identified, namely - the purpose, objectives, components, indicators, approaches and methods to analysis and evaluation.
Keywords: strategic sectors of the economy; financial security; state structural policy; economic security of the state; analysis methodology